Outcome Measurement Instruments and Evidence-based Recommendations for Measurement of the Pelvic Girdle Pain Core Outcome Set (PGP-COS): A Systematic Review and Consensus Process - Remus, Alexandria (CHURCHILL LIVINGSTONE, 2023)
10.1016/j.jpain.2022.08.003